Pengaruh Diskon dan Shopee Live terhadap Belanja Impulsif di Solo - Laksmana Dirgantara Prayoga Putra; Rheza Aditya Firmansyah; Ukkasyah Dhiyaa Uddin; Diandra Raisadewa; Reyhan Darmawan; Burhan Permata; Alvin Valerin (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
The phenomenon of impulsive buying has been on the rise during major promotional events such as 12.12, where e-commerce platforms compete to offer significant discounts and interactive shopping experiences to attract consumers. These events often leverage a combination of competitive pricing strategies and live streaming features like Shopee Live to drive spontaneous purchasing behavior. This study aims to analyze the influence of Price and Shopee Live on impulsive buying behavior among consumers in Solo. A quantitative method was employed, utilizing primary data collected through surveys of 60 respondents. The respondents were Solo residents aged over 18 who had used Shopee Live and had experience shopping via the feature. The data was analyzed using multiple linear regression, with classical assumption tests such as normality, multicollinearity, heteroscedasticity, and autocorrelation to ensure the validity of the results. The findings reveal that both Price and Shopee Live significantly influence impulsive buying behavior. The significance value for the Price variable was 0.020, while the Shopee Live variable showed a significance value of 0.000, indicating a more dominant influence of the live streaming feature. Price affects impulsive buying behavior through consumers' perception of product value, while Shopee Live, with its real-time interaction and exclusive promotions, creates urgency and strong emotional appeal, encouraging unplanned purchases. These findings underscore that a competitive pricing strategy, when combined with interactive features like Shopee Live, can effectively enhance product appeal and drive impulsive buying behavior during major events like 12.12. This study provides practical implications for e-commerce businesses to design integrated marketing campaigns by leveraging Shopee Live as a tool to enhance customer loyalty and encourage spontaneous purchases, particularly in the increasingly competitive digital shopping era. Keywords: price, Live Shopee, Compulsive Buying